Shear wave elastography of the supraspinatus tendon with early degeneration in asymptomatic type II diabetes mellitus patients: a multicenter study - Tong Wang; Yanni He; Wenhong Yi; Huiyu Xie; Dan Wang; Jie Zeng; Jinying Liang; Yufan Chen; Qiuyan Mo; Meijun Zhou; Sushu Li; Feifei Huang; et al. (BMC Musculoskeletal Disorders)
Abstract Objectives This study aimed to explore conventional ultrasound sonography and shear wave elastography (SWE) changes in the supraspinatus tendon in type 2 diabetes patients (T2DM) without shoulder pain. The factors influencing supraspinatus tendon thickness and shear wave velocity (SWV), which are measured by SWE, were also explored. Methods This multicenter study recruited nonshoulder pain individuals, including healthy and diabetic patients from March 2021 to October 2022. Propensity score matching was used to overcome selection bias. The thickness and SWV of the bilateral supraspinatus tendons were measured, and their influencing factors were evaluated via regression analysis. The sonography and blood flow signals were observed and compared via χ2 tests. Results A total of 107 T2DM patients and 270 healthy people were enrolled (mean age, 42 years ± 14, 162 men). Although 59.8% of T2DM patients without shoulder pain, they were likely to have degenerative ultrasonic image and a lower SWV (-0.529 [-0.827, -0.232] vs. 1; p = 0.001) than healthy people, but no difference was detected for uneven thickening of the tendon (p = 0.055) or blood flow signals (p = 0.060). Furthermore, subjects > 50 years old, with a BMI ≥ 25.0 and who were of Chinese Zhuang population had thicker supraspinatus tendons than did the controls. Chinese Han population and regular upper limb exercise subjects had greater tendon SWV than did controls. Conclusions SWE is a repeatable and early tool for assessing supraspinatus tendon degeneration in asymptomatic patients with T2DM. Active control of the condition of diabetes patients and regular upper limb exercise might help delay the degeneration of supraspinatus tendons.